PENDIDIKAN NILAI KEJUJURAN BERBASIS KELAS DI MADRASAH IBTIDAIYAH NEGERI 1 BANTUL YOGYAKARTA (EDUKASIA, 2019)
This study specifically aims to find out the implementation of honesty values education in students through madrasah class and to find the actualization changes  of students' honesty values after the implementation of honesty values education through madrasah class and culture at MIN 1Bantul. The research method used is Action Research. The research subjects were obtained by purposive sampling and snowball sampling. Data collection was done through observation, in-depth interviews, field notes, and documents, as well as questionnaired.The data were analyzed by using  descriptive statistics which were presented in tables, percentages,and diagram. The results of changes that occur in students' attitudes and behaviors after learning development actions by integrating honesty values in learning Science, Mathematics, Social Sciences and Indonesian and developing madrasah culture, the actualization of honesty values increases.